Cross-Platform Bayesian Optimization System for Autonomous Biological Assay Development. (December 2021) - Elder, Sam; Klumpp-Thomas, Carleen; Yasgar, Adam; Travers, Jameson; Frebert, Shayne; Wilson, Kelli M.; Zakharov, Alexey V.; Dahlin, Jayme L.; Kreisbeck, Christoph; Sheberla, Dennis; Sittampalam, Gurusingham S.; Godfrey, Alexander G.; et al.
Current high-throughput screening assay optimization is often a manual and time-consuming process, even when utilizing design-of-experiment approaches. A cross-platform, Cloud-based Bayesian optimization-based algorithm was developed as part of the National Center for Advancing Translational Sciences (NCATS) ASPIRE (A Specialized Platform for Innovative Research Exploration) Initiative to accelerate preclinical drug discovery. A cell-free assay for papain enzymatic activity was used as proof of concept for biological assay development and system operationalization. Compared with a brute-force approach that sequentially tested all 294 assay conditions to find the global optimum, the Bayesian optimization algorithm could find suitable conditions for optimal assay performance by testing 21 assay conditions on average, with up to 20 conditions being tested simultaneously, as confirmed by repeated simulation. The algorithm could achieve a sevenfold reduction in costs for lab supplies and high-throughput experimentation runtime, all while being controlled from a remote site through a secure connection. Based on this proof of concept, this technology is expected to be applied to more complex biological assays and automated chemistry reaction screening at NCATS, and should be transferable to other institutions. Graphical Abstract: